Christ Our Hope : An Introduction to Eschatology - O'Callaghan, Paul, 1956- (Book collections on Project MUSE., 2011)
Christ Our Hope is a masterful reflection on Christian eschatology, in a textbook of twelve accessible chapters. Paul O'Callaghan considers the return of Christ in glory at the end of time, final resurrection, the renewal of the cosmos, and general judgment. An extensive chapter explores eternal life, perpetual communion with God in heaven, as well as perpetual condemnation, the possibility of forever losing what God has promised to those who are faithful to him. The guiding principle of the work is the theological virtue of hope, in keeping with Benedict XVI's 2007 encyclical, Spe Salvi. The book also considers the impact of hope on the earthly life of the believer, and especially the process of the purification of hope through death and purgatory.